2010
DOI: 10.3892/ol.2010.230
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a fusion expression plasmid containing the G250 gene and human granulocyte-macrophage colony stimulating factor and its significance in renal cell carcinoma

Abstract: Abstract. This study aimed to construct a eukaryotic expression plasmid containing the G250/MN/CA IX (G250) and human granulocyte-macrophage colony stimulating factor (hGM-CSF) genes, and to detect the expression of these proteins in vitro by recombinant plasmids in eukaryotic cells. pORF-hGM-CSF and pcDNA3.0-G250 were used as the template to amplify G250 and hGM-CSF by routine polymerase chain reaction (PCR). The two PCR products were cloned into the eukaryotic vector pVAX1, in order to construct a recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…GM-CSF was used as a tumor therapy for the first time by Dranof and colleagues [13]; they found that GM-CSF produced a stronger and longer-lasting anti-tumor effect compared with their control group or other cytokines (IFN-γ, TNF-α and IL-2). To increase the immunogenicity and effectiveness of DNA vaccines, many studies [14] have fused GM-CSF with a specific antigen to make a molecular adjuvant. By doing this, humoral and cellular immune responses are significantly enhanced, tumor growth is inhibited, and the survival of experimental animals is improved.…”
Section: Functional Studies Of the Dna Vaccinementioning
confidence: 99%
“…GM-CSF was used as a tumor therapy for the first time by Dranof and colleagues [13]; they found that GM-CSF produced a stronger and longer-lasting anti-tumor effect compared with their control group or other cytokines (IFN-γ, TNF-α and IL-2). To increase the immunogenicity and effectiveness of DNA vaccines, many studies [14] have fused GM-CSF with a specific antigen to make a molecular adjuvant. By doing this, humoral and cellular immune responses are significantly enhanced, tumor growth is inhibited, and the survival of experimental animals is improved.…”
Section: Functional Studies Of the Dna Vaccinementioning
confidence: 99%
“…Renal cell carcinoma (RCC), accounting for 80%–90% of the renal tumors, is a common malignant tumor of the genitourinary system 1,2. Approximately 75%–85% of the RCC cases are clear cell RCC (ccRCC) 3,4.…”
Section: Introductionmentioning
confidence: 99%
“…Around one-third of the patients diagnosed with RCC already have locally advanced or metastatic disease. The metastasis of RCC is the leading cause of the high mortality rate in patients with RCC 2,5,6. Therefore, the study of the molecular mechanism of the occurrence, development, and metastasis of RCC and the identification of new specific early diagnostic biomarkers and therapy targets for RCC are imperative.…”
Section: Introductionmentioning
confidence: 99%
“…CAIX shows apparent tumor specificity and could serve as an ideal target for immunotherapy of renal carcinoma (13). So far, there have been many studies for CAIX antigen-based renal carcinoma vaccine, including peptide vaccine, CAIX antigen-loading dendritic cells (DC), and DNA vaccine (14,15). Remarkable progress has been observed in the development of vaccines, but the therapeutic effect and safety problem remain challenging (16).…”
Section: Introductionmentioning
confidence: 99%